Real-time assessment and neuromuscular training feedback techniques to prevent anterior cruciate ligament injury in female athletes - Myer, G. D.; Brent, J. L.; Ford, K. R.; Hewett, T. E. (Strength and Conditioning Journal, 2011)
Some athletes may be mroe susceptible to at-risk knee positions during sports activities, but the underlying causees are clearly defined. This article synthesizes in vivo, in vitro. and in silico (ciomputer-simulated) data to delineate likely risk factors to the mechanism(s) of noncontact anterior crusiate ligament (ACL) injuries. From thsi identified risk factors we will discuss newly developed rea-time screening techniques that can be used in training sessions to identify modifiable risk factors. Techniques provided will target and correct altered mechanics that may reduce or eliminate risk factors and aid in the prevention of noncontact ACL injuries in high-risk athletes.ATHLETES